Membrane-Chromatography-Reactor-System for the Continuous Synthesis of Galactosyl-Oligosaccharides - Engel, Larisa; Ebrahimi, Mehrdad; Czermak, Peter (My University, 2008)
Galactosyl-oligosaccharides (GOS) are non-digestible oligosaccharides which are qualified as functional foods. GOS are enzymatically synthesized from lactose by transgalactosylation catalyzed by the enzyme β-galactosidase. In this study, a method for immobilization of β-galactosidase from Kluyveromyces lactis on a chromatography membrane was developed. The immobilization was performed at 4, 15 and 40°C. A strong basic anion exchange membrane was investigated. In static experiments the highest enzyme activity was measured at an immobilization procedure temperature of 15°C. The immobilization on the chromatography membranes was found to be very rapid likely due to ionic adsorption. The synthesis of GOS was carried out in a Continuous Membrane Chromatography Reactor System (CMCRS) at 40°C and pH 7.0 using 20 wt% initial lactose concentration. The chromatography membranes proved to be a good support for the continuous process at high convective flow rates in the enzyme reactor system. Up to 82 % lactose conversion with 24 % GOS yield was achieved at different fluxes. The corresponding reactor productivity for the production of GOS from lactose in the CMCRS was 98.7 g GOS per hour and cubic centimeter membrane volume, which significantly exceeds previously reported results.
Keywords: Immobilization; Galactosyl-oligosaccharides; Membrane chromatography